Study on the blood glucose management with controlled goal feed in Malaysian critically ill patients - Zafirah R.C.; Ummu K.J.; Khalijah K.; Luqman H.M.; Aishah A.F.Q.A.; Azrina R.; Basri M.N.M.; Fatanah S.; Normy N.A.R. (Institute of Physics Publishing, 2023)
Blood; Glucose; Insulin; Medical computing; mHealth; Nutrition; Physiological models; Stars; Stochastic systems; Blood glucose level; Blood glucose management; Critically-ill patients; Current practices; Diabetes patients; Intensive insulin therapies; Patient specific; Virtual patients; Intensive care units